2000
DOI: 10.1037/0022-3514.79.4.631
|View full text |Cite
|
Sign up to set email alerts
|

Stalking the perfect measure of implicit self-esteem: The blind men and the elephant revisited?

Abstract: Recent interest in the implicit self-esteem construct has led to the creation and use of several new assessment toots whose psychometric properties have not been fully explored. In this article, the authors investigated the reliability and validity of seven implicit self-esteem measures. The different implicit measures did not correlate with each other, and they correlated only weakly with measures of explicit self-esteem. Only some of the implicit measures demonstrated good test-retest reliabilities, and over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

89
927
12
16

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 905 publications
(1,047 citation statements)
references
References 53 publications
(97 reference statements)
89
927
12
16
Order By: Relevance
“…This combination of a small correlation between the implicit and explicit measures of extraversion, and a heterotrait-monomethod correlation between two reliable IAT measures is what is expected on the basis of the reliable contamination hypothesis. However, besides interindividual differences in task-switching costs, several other factors may have contributed to the low implicit-explicit correlation obtained in Experiment 3, such as balancing of compatibility order (Asendorpf et al, 2002), and differences in the constructs tapped by implicit and explicit measures (Bosson et al, 2000;Wilson, Lindsey, & Schooler, 2000). Additionally, procedural variations like a relatively long response-stimulus interval of 800 ms and the incorporation of task-repetition trials may have played a role.…”
Section: Discussionmentioning
confidence: 93%
“…This combination of a small correlation between the implicit and explicit measures of extraversion, and a heterotrait-monomethod correlation between two reliable IAT measures is what is expected on the basis of the reliable contamination hypothesis. However, besides interindividual differences in task-switching costs, several other factors may have contributed to the low implicit-explicit correlation obtained in Experiment 3, such as balancing of compatibility order (Asendorpf et al, 2002), and differences in the constructs tapped by implicit and explicit measures (Bosson et al, 2000;Wilson, Lindsey, & Schooler, 2000). Additionally, procedural variations like a relatively long response-stimulus interval of 800 ms and the incorporation of task-repetition trials may have played a role.…”
Section: Discussionmentioning
confidence: 93%
“…However, in IAT research it is rare to find substantial (positive) correlations between different implicit measures designed to assess the same concept. For example, Bosson et al (2000) assessed measures of implicit self-esteem and found very low and (often) non-significant correlations. This is often explained by the fact that even subtle changes in a task can trigger different associative processes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that correlations between affective priming effects and criterion variables are sometimes small or even absent (e.g., Banse, 1999Banse, , 2001Bosson, Swann, & Pennebaker, 2000). In part, this fact seems to be related to the on-average-limited reliability of affective priming scores.…”
Section: Affective Priming Effects the What Criterion: What Attributementioning
confidence: 99%